RELATIONSHIP BETWEEN DIET AND GASTRITIS INCIDENCE IN ADOLESCENTS IN BOJONGGEDE VILLAGE - Hikmah, Wa Ode Erty; Mustikawati, Mustikawati; Khoirunnisa, Umi; Lestari, Dyah (International Journal of Health Science & Medical Research, 2025)
Gastritis is one of the non-communicable diseases with a very high incidence. In Indonesia, gastritis is even included in the 10 most common diseases and occurs in all age groups. The incidence of gastritis is partly caused by irregular diet or a good diet. The purpose of this study is to determine the relationship between diet and the incidence of gastritis in adolescents in Muara Village, Bojonggede. This research method uses a cross-sectional design. The number of respondents in this study was 72 respondents. The sampling technique used in this study is simple random sampling. The statistical test used in this study is the Chi Squared Test. The results of the study showed that the incidence of gastritis in Muara Village and Perigi Village was only 15 respondents (20.8%). The results of the chi square test obtained the results of Asymp. Sig 0.737 with a significance level of 0.05. If Asymp. Sig 0.05 then there is a significant relationship, if the Asymp. Sig value 0.05, then there is no significant relationship. Thus, it can be interpreted that there is no relationship between diet and the incidence of gastritis. This can also be interpreted that a person's diet has no correlation with the incidence of gastritis. Conclusion from this study there is no relationship between diet and the incidence of gastritis in Muara Village and Perigi Village.